A Conservative Modification to the Ghost Fluid Method for Compressible Multiphase Flows (Communications in Computational Physics, 2011)
A conservative modification to the ghost fluid method (GFM) is developedfor compressible multiphase flows. The motivation is to eliminate or reduce the conservationerror of the GFM without affecting its performance. We track the conservativevariables near the material interface and use this information to modify the numericalsolution for an interfacing cell when the interface has passed the cell. The modificationprocedure can be used on the GFM with any base schemes. In this paper we use thefifth order finite difference WENO scheme for the spatial discretization and the thirdorder TVD Runge-Kutta method for the time discretization. The level set method isused to capture the interface. Numerical experiments show that the method is at leastmass and momentum conservative and is in general comparable in numerical resolutionwith the original GFM.